Multi-level issues in organizational behavior and leadership - Yammarino, Francis J., 1954-; Dansereau, Fred, 1946- (Emerald, 2009)
Multi-Level Issues in Organizational Behavior and Leadership is Volume 8 of Research in Multi-Level Issues, an annual series that provides an outlet for the discussion of multi-level problems and solutions across a variety of fields of study. Similar to Volumes 1 through 7, this volume contains five major essays with commentaries and rebuttals that cover a range of topics, but in the realms of organizational behavior and leadership. In particular, the five 'critical essays' offer extensive literature reviews, new model developments, methodological advancements, and some data for the study of organizational behavior, outstanding leadership, leadership and social relations, leadership simulation, and enviroscapes. While each of the major essays, and its associated commentaries and rebuttals, is unique in orientation, all of the essays share a common bond in raising and addressing multi-level issues or discussing problems and solutions that involve multiple levels of analysis in organizational behavior and leadership.
Keywords: Leadership.; Organizational behavior.; elektronické knihy; electronic books